Integrated Crop Management Practices of Wheat through Frontline Demonstration in Bundelkhand Region - Singh, Anil Kumar (Indian Journal of Extension Education, 2021)
Krishi Vigyan Kendra, Datia, Madhya Pradesh conducted 365 demonstrations on wheat varieties GW-366 and RVW-4106 during 2017-18 to 2020-21 at farmers’ field in Datia district to find out the worth of the improved technology. The parameters like technological impact, economical impact and extension gap were analyzed and the feasibility of demonstrated technologies at grass root levels was assessed. The results of four years of studies revealed that the yield under demonstration plots was 4684 kg/ha as compared to 3875 kg/ha in traditional farmer practices plots. This additional yield of 809 kg/ha and the increase in average wheat productivity by 21.43 per cent may contribute to the present wheat requirement on national basis. The average technology gap, extension gap and technology index were found to be 376.50 kg/ha, 807.75 kg/ha and 7.40 per cent respectively. An additional investment of Rs. 1470 per ha coupled with scientific monitoring of demonstrations and non-monetary factors resulted in an additional net return of Rs. 13531 per ha. Fluctuation in the sale price of wheat during different years influenced the economic returns per unit area. On four years overall average basis incremental benefit cost ratio was found as 3.41. The results indicate the positive effects of FLDs over the existing practices.
Keywords: Benefit cost ratio; Extension gap; Technology gap; Technology index